Parking Systems Development’s Model in Malang City - Susanto, Roedy; Z. Fanani; Mohammad Nuh; Setyo Widagdo (Technium Social Sciences Journal, 2020)
With a high level of urbanization, Malang City and surrounding areas face complex problems which related to housing and citizen mobility. Citizens’ mobility is one of the main problems, because the unavailability of an appropriate public transportation system, which caused residents prefer to use private vehicles. The use of private vehicles has a direct impact on congestion problems in the urban areas and city boundaries. This condition is exacerbated by poorly arranged parking management in Malang. Most of the parking areas in Malang are parking on the roadside which automatically reduces the area of the highway. In addition, parking activities on the roadside have the potential to disrupt the smooth operation which caused by parking activities. The design of the parking area infrastructure which according to the needs based on the characteristics of the used land is very much needed.